Comparative Analysis of Concrete and Reinforcement Work Volume Using Building Information Modelling Support Software - Hasbi, Edlin Al Khuzaifah; Susanti, Betty; Adhitya, Bimo Brata (Universitas Islam 45, 2025)
The era of the 4.0 revolution has four principles consisting of interconnection, information transparency, technical assistance, and decentralized decision-making. Four principles can be the guidelines for the Building Information Modelling (BIM) system. Government building projects have rules that stipulate that the BIM system must be applied in every construction project. The purpose of this study is to compare the volume of plan and realization work from contractors with conventional methods with plan and realization modeling on pilecap, column, and beam work for concrete and reinforcing work. The method used in this study is to make concrete and reinforcing modeling using Glodon Cubicost TAS and TRB software and use comparative analysis for each work volume result from conventional calculations and BIM modeling results. The data needed consists of general building data, plan drawing data and realization, as well as calculation of the volume of concrete and reinforcement. The results of the study show that there is a varied percentage difference between the data from the contractor and the modeling made, both plans and realization. The use of this software is considered effective if it has been used since the beginning of the construction project, because it can reduce errors and improve the integration between RAB and plan drawings as well as RAP and As Built Drawing.